Peer Tutor Method to Improve Problem Posing Ability - Isrokatun, Isrokatun; Rosmiati, Rosi; Hanifah, Nurdinah; Rohman, Yusuf Abdul (Universitas Pendidikan Indonesia, 2023)
This study was conducted to determine the description of learning with the peer tutor method implemented through situation-based learning. The urgency of this study is to find out the problem posing ability of elementary school students as an intellectual skill that students must possess to support future competition. From the existing problems, students are accustomed to receiving knowledge without posing the problems they find. The peer tutor method through SBL facilitates students in problem-posing ability, problem-solving, and independent learning. The peer tutor method makes it easier for teachers to provide structured guidance to facilitate students through discussions. This study employed a descriptive qualitative method involving fourth-grade students, in which the data were obtained using observation, interview, and documentation guidelines. The obtained data were reduced to be able to conclude. This study found that learning through the peer tutor method involves active student roles, facilitates students to construct their knowledge in a guided manner, creates meaningfulness in students in posing problems, leads to follow-up questions, and responses to the problems posed.